2008
DOI: 10.1086/523837
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Dense Core Population in the Pipe Nebula: Thermal Cores Under Pressure

Abstract: In this paper we present the results of a systematic investigation of an entire population of predominately starless dust cores within a single molecular cloud, the Pipe Nebula. Analysis of extinction data shows the cores to be dense objects characterized by a narrow range of density with a median value of n(H 2 ) ¼ 7 ; 10 3 . The nonthermal velocity dispersions measured in molecular emission lines are found to be subsonic for the large majority of the cores and show no correlation with core mass (or size). Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
277
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(323 citation statements)
references
References 53 publications
(69 reference statements)
43
277
3
Order By: Relevance
“…André et al André et al 2010 andKönyves et al 2010). For comparison, the locations of the (sub)mm continuum prestellar cores identified by Motte et al (1998Motte et al ( , 2001 in ρ Oph and NGC2068/2071, respectively, are shown, along with the dust extinction cores of the Pipe nebula (Alves et al 2007, Lada et al 2008, and the correlation observed for diffuse CO clumps (shaded band -cf. Elmegreen & Falgarone 1996).…”
Section: First Results From Herschel On the Cmf-imf Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…André et al André et al 2010 andKönyves et al 2010). For comparison, the locations of the (sub)mm continuum prestellar cores identified by Motte et al (1998Motte et al ( , 2001 in ρ Oph and NGC2068/2071, respectively, are shown, along with the dust extinction cores of the Pipe nebula (Alves et al 2007, Lada et al 2008, and the correlation observed for diffuse CO clumps (shaded band -cf. Elmegreen & Falgarone 1996).…”
Section: First Results From Herschel On the Cmf-imf Connectionmentioning
confidence: 99%
“…This finding is reminiscent of the CMF results obtained with ground-based (sub)millimeter dust continuum observations, although most of the starless cores in the Pipe Nebula are gravitationally unbound objects confined by external IAUS 270. Prestellar core mass functions and link to the IMF 257 pressure (Lada et al 2008). Hence, a large fraction of them do not qualify as prestellar cores and may never evolve into stars.…”
Section: Prestellar Core Mass Functions From Ground-based Observationsmentioning
confidence: 99%
“…In an idealized case, a constant volume density trend is expected if IRDC cores are in pressure balance (cf. the Pipe Nebula, Lada et al 2008). However, there are several observational issues one must keep in mind.…”
Section: Irdc Small-scale Structurementioning
confidence: 99%
“…1.2. Second, a radius was calculated for the core from the mass-to-radius relation log 2R = 0.35 × log M + 0.65 that was derived for the cores of the Pipe nebula by Lada et al (2008). In the equation, R is given in arcminutes and M in solar masses.…”
Section: Simulated Extinction Mapsmentioning
confidence: 99%
“…The procedure is the same as used by ALL07, and it is outlined in their paper (see also Sect. 2.1 of Lada et al 2008). First, the extinction map was decomposed with a wavelet transformation at 4 scale.…”
Section: The Core Extractionmentioning
confidence: 99%